Bones and joints a guide for students - Gunn, Christine (Churchill Livingstone/Elsevier, 2012)
Printed book plus Pageburst access - you will receive a printed book and access to the complete book content electronically. Pageburst enhances learning by not only bringing world class content to your fingertips but also letting you add to it, annotate it, and categorize it all in a way that suits you. Pageburst frees you to spend more time learning and less time searching. This book is a clear, concise introduction to the subject which covers all the major bones and joints in the body in a logical and systematic way to aid understanding. The three generic chapters at the start of the book, covering an overview of bone, joints and pathology, provide the basic information required to ensure that the student is able to gain the most benefit from the subsequent area-specific chapters. The text is written in note form and the drawings are as clear and simple as possible so that they can be easily reproduced by students. In this edition a number of the radiographic images have been improved and replaced and the number of imaging techniques has increased by including PET and SPECT images